TINJAUAN KELENGKAPAN PENGISIAN RESUME MEDIS RAWAT INAP DI RUMAH SAKIT BHINEKA BAKTI HUSADA - SUCIPTO, SUCIPTO; Purwaningsih, Neneng Sri; Junetri, Syakilla Dwi (STIKes Widya Dharma Husada Tangerang, 2022)
ABSTRACTBackground: Medical resume is an information record containing the identity, examination results and doctor's authentication. Medical resume must be filled in completely after the patient returns home within 1x24 hours. Research Purposes : Describe and describe how the completeness of the Indonesian medical resume at the Bhineka Bakti Husada Hospital. Research Methods : namely descriptive research looking at causal relationships carried out by collecting data on the population with 1 certain time period. Result: The mean of completeness of identity is 78.48% Mostly complete and 21.52% Somely incomplete. The average of completeness in important reports is 84.68% Most are complete and 15.32% Some are incomplete. The average completeness of the doctor's authentication is 82,92% Some are complete and the average of the incomplete doctor's authentication is 17.09% a small part is incomplete. The obstacle in filling out the RI medical resume at the BBH Hospital is the busyness of doctors causing incompleteness in filling out the medical resume. Conclusion: There is no SOP in the medical resume at BBH Hospital. Completeness of identity in medical resume Most are complete and almost half are incomplete. The results of the completeness of important reports are all complete and almost half are incomplete tidak. Suggestion: SOP for RI medical resume was made. Remind the doctor to fill out the RI medical resume. Conducting socialization with the hospital director, medical committee, doctors and RM staf. ABSTRAKLatar Belakang: Resume medis yaitu catatan informasi yang berisikan identitas, hasil pemeriksaan dan autentifikasi dokter. Resume medis harus diisi lengkap setelah pasien pulang dalam kurun waktu 1x24 jam. Tujuan Penelitian: Menggambarkan dan menguraikan bagaimana kelengkapan resume medis RI di RS Bhineka Bakti Husada. Metode Penelitian: yaitu penelitian deksriptif melihat hubungan sebab akibat yang dilakukan dengan cara pengambilan data pada populasi dengan 1 periode waktu tertentu. Hasil: Rata-Rata dari kelengkapan identitas adalah 78,48% Sebagian besar lengkap dan 21,52% Sebagian kecil tidak lengkap. Rata-rata dari kelengkapan pada laporan penting adalah 84,68% Sebagian besar lengkap dan 15,32% Sebagian kecil tidak lengkap. Rata-rata kelengkapan pada autentifikasi dokter 82,92% Sebagian lengkap dan rata-rata dari ketidaklengkapan autentifikasi dokter adalah 17,09% Sebagian kecil tidak lengkap. Kendala dalam pengisian resume medis RI di RS BBH yaitu kesibukan dokter menyebabkan ketidaklengkapan dalm pengisian resume medis. Kesimpulan: SOP dalam resume medis di RS BBH tidak ada. Kelengkapan identitas dalam resume medis Sebagian besar lengkap dan hampir setengahnya tidak lengkap. Hasil dari kelengkapan laporan penting seluruhnya lengkap dan hampir setengahnya tidak lengkap. Saran: Dibuatkan SOP resume medis RI. Mengingatkan dokter untuk mengisi resume medis RI. Mengadakan sosialisasi bersama direktur RS, komite medik, dokter dan staff RM.